Legal Protection for Business Actors and Consumers in E-Commerce Digital Business - Ana Seila (Penerbit Hellow Pustaka, 2025)
The development of information and communication technology has driven rapid growth in the business sector, especially in the e-commerce sector. People now prefer to shop online through platforms such as Shopee, Lazada and TikTok, which offer convenience, competitive prices and good product quality. However, with the increase in electronic transactions comes a variety of legal challenges that need to be addressed, including the risk of fraud, low-quality products, and a lack of information transparency. Legal protection for business actors and consumers is a crucial issue in this context. In Indonesia, regulations such as Law Number 8 of 1999 concerning Consumer Protection and Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) have been implemented to protect the rights of both parties. However, challenges in implementation and enforcement remain, given the dynamic nature of technology and changing consumer behavior. This article discusses relevant aspects of legal protection, the challenges faced, as well as recommendations for strengthening legal protection for businesses and consumers in the e-commerce ecosystem.